QUALITY IMPROVEMENT ON CERAMIC TILES PROUCTION PROCESS WITH SIX SIGMA METHOD (DMAIC) AT PT ARWANA CITRAMULIA - Priskila Christine Rahayu; Vanesa Darvin (Journal Industrial Manufacturing, 2018)
This study focused on quality improvement on ceramic tiles production process at PT Arwana Citramulia. This study used data defects for 12 months (May 2016 – April 2017) and only focus on one type of defect and it is chop corner. Six sigma with DMAIC (define, measure, analyze, improve, and control) approach was used to improve the process. Each step of DMAIC was conducted to carefully analyze and keep the process precisely. The ceramic tiles production process contains a number of 4375 products defects in million opportunities (DPMO), with sigma level of 4.13. In the improve step of DMAIC, FMEA form was used to propose some recommendations in order to improve the process, some of that that are provision of lubricant periodically by the operator, polishing on the surface of the liner to clean and clear, examination and maintenance periodically. Keyword : Quality, Six Sigma, DMAIC, Defects.